1,4-Phenylenebis(methylene) dicarbamate - Li, Zhi (International Union of Crystallography, 2012)
The title compound, C(10)H(12)N(2)O(4), is a phenyl dicarbamate with crystallographically imposed inversion symmetry. The dihedral angle between the carbamoyloxy plane [i.e. the plane of the N—C(O)—O fragment; r.m.s. deviation = 0.002 (3) Å] and the plane of the aryl ring is 29.2 (1)°. In the crystal, two different centrosymmetric N—H⋯O hydrogen-bond interactions are observed; these are described as R (2) (2)(8) and R (2) (4)(8) in graph-set notation. The rings form an alternating sequence, linking the molecules into a sheet structure parallel to (011).